The tax environment of administrative rules and other tax and constitutional provisions - Margin Manautou, Emilio (UNIVERSIDAD DE SONORA, 2018)
The document examines the legal and fiscal scope of the administrative rules and other tax and constitutional provisions in Mexico, by contrasting the theoretical aspect of the concept with the provisions of federal fiscal legislation, in light of the interpretation made by The Judicial Power in specific cases, highlighting the similar situation observed in certain cases of judicial intervention that blocks or invalidates United States Executive´s administrative rules, by contravention of the principle of legal hierarchy.